2010
DOI: 10.1097/aln.0b013e3181f5d32d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pregabalin as an Adjuvant to Patient-controlled Epidural Analgesia during Late Termination of Pregnancy

Abstract: Introduction: Late termination of pregnancy combines psychological distress with severe physical pain. The present study evaluated the benefit of adding oral pregabalin to epidural analgesia during this procedure. Methods: Healthy women were randomly allocated to receive either oral pregabalin 150 mg/12 h or prazepam 10 mg/12 h at the induction of the late termination of pregnancy procedure. When they felt abdominal pain (numerical rating scale ranging from 0 [no pain] to 100 [worst pain possible]), patientcon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Analgesia was measured according to VAS score in immediate postoperative period and follow up was done till 6 hour. This study has similar findings with that of Jokela et al (2008) [22], Sarawat et al [23], Peng et al [24], Patricia et al [25], Burke et al [26], Kim et al [27], Mathiesen et al [28]. All these have reported the analgesic property of pregabalin.…”
Section: Discussionsupporting
confidence: 80%
“…Analgesia was measured according to VAS score in immediate postoperative period and follow up was done till 6 hour. This study has similar findings with that of Jokela et al (2008) [22], Sarawat et al [23], Peng et al [24], Patricia et al [25], Burke et al [26], Kim et al [27], Mathiesen et al [28]. All these have reported the analgesic property of pregabalin.…”
Section: Discussionsupporting
confidence: 80%
“…50 mg and it was found that the time for need of rescue analgesia was significantly more in pregabalin groups than control group and significant difference was found between 2 doses of pregabalin in this respect. These findings are in accordance to Jokela et al, [16] Sarawat et al, [17] Peng et al, 18 Patricia et al, [19] Burke et al, [20] Kim et al [21] They all reported the good analgesic property of pregabalin. Various mechanisms may contribute to pregabalin analgesic property such as the modulation of visceral pain and central sensitisation.…”
Section: Discussionsupporting
confidence: 81%
“…One‐hundred and six references were obtained, in which 22 published studies on the perioperative use of pregabalin met our inclusion criteria 5–6,10–29 …”
Section: Resultsmentioning
confidence: 99%
“…The duration of assessment for post‐operative pain was for 1 day or less in 10 studies, 6,10,11,17,18,20–23,27 for 2 days in three studies, 12,13,19 for 3 days in one study 13 and for 7 days in three studies 14,24,29 …”
Section: Resultsmentioning
confidence: 99%